A comparison of post-match recovery strategies in youth soccer players - Kinugasa, T.; Kilding, A. E. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to determine the effect of 3 post-match recovery modalities on physical performance, physiological measures, and players' perceptions of recovery after 90-minute soccer match play. On separate days, 28 young (age: 14.3 ± 0.7 years) soccer players played 3 soccer matches each randomly followed by 1 of 3 recovery modalities: (a) CONT-cold (12° C) water immersion and hot (38° C) shower, (b) COMB-cold water immersion and active recovery using a cycle ergometer, and (c) PASS-a passive post-match routine (stretching and leg raise). Performance (vertical jump height), physiological (heart rate and tympanic temperature), and perceptual measures (perceived quality of recovery) were determined before each match, 10 minutes after each match, after each recovery method, and after 24 hours. There was a 0.6 ± 6.7% drop in immediately after a match, but there was no difference in vertical jump height after 24 hours (p = 0.997). Perceived quality of recovery immediately after COMB was substantially higher than CONT and PASS, but the effect did not last more than 24 hours. The players perceived lighter legs after COMB, compared with the PASS, at post-24 hours. In conclusion, a combined recovery modality (cold water immersion and active recovery) after a soccer match did not have a substantial effect on vertical jump height performance when compared with contrast water immersion and passive recovery alone. However, the observed positive effects on perceived recovery (higher quality of recovery and lighter legs) after the combined modality (cold water immersion and active recovery) suggest that this approach may be effective for young players after intense soccer match play.